O Acervo Fotográfico da Reitoria Da Ufes: Informação, Memória e Patrimônio Documental - Modolo, Philippe Peterle (2024)
This study investigates the role of photograph collections from the UFES rectory's office in maintaining institutional memory. Starting from the question about the photographic document and its relationship with the mechanisms of memory, the work investigates the photograph present in the university archive as a document and as a source of information, fundamental for historical reconstruction. The investigative path begins with a literature review, addressing the main studies that address university archives and their intersection with institutional memory, discussing the issue of photographic documents in contemporary times, while associating the formation of the photographic collection with the history of UFES. Then, a case study is used, aiming to make a diagnosis of the conditions of production, storage, access, and use of photographs produced during the rectors' activities. Weaving a narrative of the institutional historical trajectory and analyzing the different contexts of photography production, it identifies the sectors linked to the institution's central administration, mapping their photographic collections, to bring together the entire collection of photographs originating from the activities of the rectory's office. Its general objective is to highlight the importance of the UFES - Campus Goiabeiras photographic collection as a source of information for the maintenance of its institutional memory. The specific objectives are: Verify in the literature aspects of photography as a document and its intersection with institutional memory; Identify sectors directly linked to the central administration of UFES on the Goiabeiras Campus that have photographic collections, mapping the places that produce and archive these collections; Characterize how this collection has been formed and what this collection is composed of; Reflect the UFES photographic collection from the perspective of documentary heritage; Highlight the importance of photography for the preservation of institutional memory. Furthermore, it discusses the patrimonialization of photographic documentary collections and access to information as a cultural right. The results of the study reveal that the collection of photographs in the rectory's office documents the most significant events at the university, constituting relevant value for reconstituting history and maintaining institutional memory. It also presents as a result, the growing increase in the use of photography as a resource for recording the activities of the rectory's office. In qualitative analysis, the study demonstrates the main events that motivated the production of photographic records in each period of UFES management. Despite this, the results also indicate that, based on user registration, the collection is little known and widespread. Finally, it is concluded that despite its historical, cultural and educational relevance, the collection is in a worrying state regarding security and conservation, and therefore, recommendations are proposed for its safeguarding and greater enjoyment by society, recognizing the existence of numerous challenges that arise to ensure the preservation and full access to these collections.